Management of the Republic of Turkey fuel and energy complex: structure and legal regulation - B. D. Nuriev; S. V. Pospelov (Управление)
The article examines the management structure of the fuel and energy complex of Turkey as a system of coordinating the activities of state organisations with a certain degree of autonomy that has taken shape over the past two decades. The authors emphasise that this management system is characterised by a sign of decentralisation, which is manifested by the delegation and distribution of a number of powers between subordinate structures. It is assumed that the established tradition in management gives the system flexibility in making significant decisions, which is extremely necessary in conditions of uncertainty in the global hydrocarbon market. The article also analyses the established regulatory framework in the field of regulating the activities of management bodies in the fuel and energy complex of Turkey. The authors focus on two main documents – the president R.T. Erdogan decree, which defined the general principles of the key management body – the Ministry of Energy and Natural Resources, and the energy development plan for the period 2019–2023, which outlines the main tasks and objectives of the management bodies. Special attention is paid to issues of international cooperation. The authors believe that under the current conditions, more active cooperation between Russian and Turkish businesses will help strengthen the positions of Russian oil and gas companies in the energy market in the Eastern Mediterranean, the Middle East and the European Union. In the course of the research, both general theoretical methods of scientific cognition characteristic of most branches of science and special methods used in such branches of knowledge as management theory, law and economics found practical application.